TYK2 :p.Pro1104Ala Variant Protects Against Autoimmunity by Modulating Immune Cell Levels - Steri, Maristella; Orrù, Valeria; Sidore, Carlo; Mulas, Antonella; Pitzalis, Maristella; Busonero, Fabio; Maschio, Andrea; Serra, Valentina; Dei, Mariano; Lai, Sandra; Virdis, Francesca; Lobina, Monia; et al. (Immunology, 2025)
ABSTRACT The TYK2:p.Pro1104Ala (rs34536443) hypomorph variant has been associated with protection against numerous autoimmune disorders. Thus, its mechanism of action becomes of great interest. Here, consistent with the participation of activated immune cells in autoimmunity, we show that the variant regulates the levels of immune cells at a human, general population level and is associated particularly with higher levels of T and B lymphocytes, especially the naïve (non‐activated) compartment. Also, consistent with a protective function in autoimmunity, the level of regulatory CD4+ T cells was increased. Thus, this variant decreases immune activation thereby protecting from autoimmunity. Our work links the cellular mechanism regulated by the TYK2:p.Pro1104Ala variant to autoimmunity protection and supports TYK2 as a therapeutic target in autoimmunity. TYK2:p.Pro1104Ala variant confers protection from several autoimmune disorders but predisposes to infection and we show that the mechanism of its action includes an increase of the levels of lymphocytes in all compartments (CD4+, CD8+ and B), but these cells are mainly naive. Thus, this variant constrains immune activation thereby protecting from autoimmunity. Our work identifies the cellular mechanisms of regulation by the TYK2:p.Pro1104Ala variant providing novel hypotheses for the general immune mechanisms of protection from autoimmunity.